(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to determine the prevalence of cognitive impairment and its associated factors among the elderly in Da Nang city. Methods: A cross-sectional study was conducted on 846 individuals aged ≥ 60 years, selected through multistage random sampling in 18 communes/wards. Cognitive impairment was assessed using the MMSE, standardized for use in Vietnam. Results: The overall prevalence of cognitive impairment was 20.6%. Prevalence increased with age: 12.8% (60-65 years), 22.3% (65-70 years), and 32.5% (> 70 years), p < 0.05. Cognitive impairment prevalence decreased significantly with higher education levels: 27.6% (primary school), 23.5% (lower secondary), 18.1% (upper secondary), and 12.1% (above high school), p < 0.05. No statistically significant differences were found by gender or economic status. Conclu Cognitive impairment, elderly, MMSE, Da Nang. sions: Cognitive impairment is common among the elderly in Da Nang and is influenced by age and educational level. These findings highlight the need for community-based screening and early intervention programs to detect and prevent cognitive impairment.